PEDAGOG KADRLAR KASBIY KOMPETENTLIGINI UZLUKSIZ RIVOJLANTIRISH MUAMMOSI - Haqnazarova, N.Q.; Mannopova, R.B.; Mashrapova, S.T. (SCIENCE and SOCIETY, 2024)
The article examines the views of scientists on ensuring the improvement and perfection of teachers’ professional skills through the continuous development of their professional competence.